The growth of firms : Middle East oil, and other essays - Penrose, Edith Tilton (London, Cass, 1971)
The book is the compilation of the essays written by the author dealing with the economics of international oil companies in developing countries as well as the politics involved.
Includes bibliographical references.
usc 28/01/2019
Loans
Keywords: International business enterprises; Industries; Petroleum industry and trade; Middle East